Marketing and managing tourism destinations - 3G E-Learning LLC (New York, NY 3G E-Learning LLC, 2023)
"Tourism Marketing is still an underdeveloped area and is often confused with selling. The tourism industry is comprised of small enterprises (travel agencies, tour operators etc.) and few among them actually adopt marketing whereas selling is done by all. However, the way tourism market is maturing, the relevance of marketing is being acknowledged more and more as an important activity for the success of the enterprise. This is also because competition is increasing. Destination management plays a vital role in helping organizations in the travel and tourism industry achieve their goals. It can unlock many benefits, such as delighting the travelers so they return to the destination, increasing revenue, and building a sustainable plan for the future. It is important for a destination managers to make their consumers (tourists) interested in their location before tourists arrive using social media marketing and other marketing tools. The destination marketing organizations are held responsible to show the privileges destination (country, region, city, town, location etc.). Destination marketing organizations mostly include creating and sharing the story about the destination they promote, which will make people interested. This edition is thoroughly revised and new chapters are added. The aim of this book is to provide the student with a general framework of the principles of tourism destination marketing. Tourism and moreover business tourism does not exist in a vacuum. It can only function if it shares, cooperates and dialogues effectively with many other sectors of society and economy. The book also explains that marketing of destinations should balance the strategic objectives of all stakeholders as well the sustainability of local resources." --
Chapter 1 Destination Marketing and Management.
Chapter 2 Consumer Behavior and Decision Making in Tourism.
Chapter 3 Destination Marketing: Research, Branding and Image Communication.
Chapter 4 Destination Product Development and Distribution.
Chapter 5 Managing Stakeholder at Destination.
Chapter 6 Safety and Crisis Management in Tourism.
Chapter 7 Sustainability and Competitiveness of Tourism.
Chapter 8 Events Tourism and Destination Management.
Index.
Editorial board: Aleksandar Mratinkovic, Dan Piestun, Hazem Shawky Fouda, Felecia Killings, Dr. Sandra El Hajj, Fozia Parveen, Igor Krunic, Dr. Jovan Pehcevski, Dr. Tanjina Nur, Stephen and Michelle.
Includes bibliographical references and index.
Keywords: Tourism -- Marketing; Tourism -- Management